(untitled) (International Educators Conference, 2025)
This article explores the role of independent education within the framework of the credit-module system (CMS) in vocational education organizations. Independent education is a cornerstone of modern learning methodologies, fostering self-regulation, critical thinking, and lifelong learning competencies. The CMS, with its modular structure and competency-based approach, provides an ideal environment for the development of independent education. This study examines the strategies, challenges, and benefits of promoting independent education in vocational settings. It also highlights the integration of digital tools, the role of faculty, and international best practices, offering recommendations for effectively incorporating independent learning into CMS-based programs.